2001
DOI: 10.1002/ajim.1057
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of occupational injuries and illnesses in a university population: A focus on age and gender differences

Abstract: These group differences suggest the need to examine age and gender job distributions and relevant ergonomic and environmental causative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…[24][25][26][27] The most commonly noted epidemiological association with CTS is high force, high repetition activity. [4][5][6][7][8][9][10][11][12] The connection, if any, between these two observations is unknown, although some studies 25,28 have shown that the SSCT of patients with CTS is less permeable than normal SSCT, and might therefore predispose to pressure elevation. Although the tensile strength and viscoelastic behavior of tendon has been well studied, [29][30][31][32][33][34][35] to date there have been no studies assessing the motion characteristics of the flexor tendons within the carpal tunnel, or even demonstrating a method to do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] The most commonly noted epidemiological association with CTS is high force, high repetition activity. [4][5][6][7][8][9][10][11][12] The connection, if any, between these two observations is unknown, although some studies 25,28 have shown that the SSCT of patients with CTS is less permeable than normal SSCT, and might therefore predispose to pressure elevation. Although the tensile strength and viscoelastic behavior of tendon has been well studied, [29][30][31][32][33][34][35] to date there have been no studies assessing the motion characteristics of the flexor tendons within the carpal tunnel, or even demonstrating a method to do so.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 It is generally accepted that repetitive, forceful hand or wrist motion, often associated with awkward wrist posture, is a risk factor for CTS, [4][5][6][7][8][9][10][11][12] but how these mechanical factors relate to the pathological changes of noninflammatory synovial thickening seen typically in cases of CTS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is often described as an occupational disease among persons who perform repetitive work with their hands (Abbas et al, 1998;Armstrong et al, 1984;Saleh et al, 2001;Stal et al, 1999;Szabo, 1998;Wu et al, 2003). The most commonly reported pathological finding is non-inflammatory fibrosis and thickening of the subsynovial connective tissue (SSCT) (Armstrong et al, 1984;Ettema et al, 2004;Kerr et al, 1992;Lluch, 1992;Nakamichi et al, 1998;Neal et al, 1987;Phalen, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is that overuse from forceful, repetitive hand motions causes cumulative trauma to structures within the tunnel. Epidemiological studies showed that highly repetitive work is related to an increased risk for CTS . In vivo studies found biomechanical alterations of the tissues within the carpal tunnel in CTS patients …”
mentioning
confidence: 99%